Temperature responsive plasmonic assembles of amphiphilic nanoparticles at oil-water interfaces. - Chan, Kevin Jin Quan. (2011)
Gold nanoparticle (AuNP) has been widely used in the biotechnology field due to its bio-inert characteristic and other unique physical qualities such as optical and electrical properties. Here, a new class of AuNP with multi-polymer brush coating, which can spontaneously assemble and disassemble under the influence of temperature, is reviewed in this report. This new class of AuNP coated with hydrophilic and hydrophobic multi-polymer brushes allows for self-assembly in temperature condition of more than 40 ̊C and disassembles in temperature condition of less than 20 ̊C in an oil-water interface.